Oral Administration of Oleuropein and Its Semisynthetic Peracetylated Derivative Prevents Hepatic Steatosis, Hyperinsulinemia, and Weight Gain in Mice Fed with High Fat Cafeteria Diet. (22nd December 2015) - Lepore, Saverio Massimo; Morittu, Valeria Maria; Celano, Marilena; Trimboli, Francesca; Oliverio, Manuela; Procopio, Antonio; Di Loreto, Carla; Damante, Giuseppe; Britti, Domenico; Bulotta, Stefania; Russo, Diego
Abstract : The high consumption of olive tree products in the Mediterranean diet has been associated with a lower incidence of metabolic disorders and cardiovascular diseases. In particular, the protective effects of olive oil have been attributed to the presence of polyphenols such as oleuropein (Ole) and its derivatives. We have synthesized a peracetylated derivative of Ole (Ac-Ole) which has shown in vitro antioxidant and growth-inhibitory activity higher than the natural molecule. In this study, male C57BL/6JOlaHsd mice were fed with a standard (std), cafeteria (caf) diet, and caf diet supplemented with Ole (0.037 mmol/kg/day) and Ac-Ole (0.025 mmol/kg/day) for 15 weeks. We observed a significant reduction in the caf diet-induced body weight gain and increase of abdominal adipose tissue. Also, Ole and Ac-Ole prevented the development of hepatic steatosis. Finally, Ole and Ac-Ole determined a lower increase of HDL and LDL-cholesterol levels and corrected caf diet-induced elevation of plasma glucose concentrations by improving insulin sensitivity. The observed beneficial properties of Ole and Ac-Ole make these compounds and in particular Ac-Ole promising candidates for a potential pharmaceutic use in metabolic disorders.